Comparative genomics reveals insight into the phylogeny and habitat adaptation of novel Amycolatopsis species, an endophytic actinomycete associated with scab lesions on potato tubers - Wannawong, Thippawan; Mhuantong, Wuttichai; Macharoen, Pipat; Niemhom, Nantawan; Sitdhipol, Jaruwan; Chaiyawan, Neungnut; Umrung, Sarinna; Tanasupawat, Somboon; Suwannarach, Nakarin; Asami, Yukihiro; Kuncharoen, Nattakorn (Frontiers in Plant Science, 2024)
A novel endophytic actinomycete, strain MEP2-6 T , was isolated from scab tissues on potato tubers collected from Mae Fag Mai Sub-district, San Sai District, Chiang Mai Province, Thailand. Strain MEP2-6 T is Gram-stain-positive and filamentous bacteria characterized by meso-diaminopimelic acid in cell-wall peptidoglycan and arabinose, galactose, glucose, and ribose in whole-cell hydrolysates. Diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, and hydroxyphosphatidylethanolamine were the major phospholipids, of which MK-9(H6) was a predominant menaquinone, while iso-C16:0 and iso-C15:0 were major cellular fatty acids. The genome of the strain was 10,277,369 bp in size with a G+C content of 71.7%. The 16S rRNA gene phylogenetic and core phylogenomic analyses revealed that strain MEP2-6 T was closely related to Amycolatopsis lexingtonensis NRRL B-24131 T (99.4%), A. pretoriensis DSM 44654 T (99.3%), and A. eburnea GLM-1 T (98.9%). Notably, strain MEP2-6 T displayed 91.7, 91.8, and 87% ANIb and 49, 48.8, and 35.4% dDDH to A. lexingtonensis DSM 44653 T (=NRRL B-24131 T ), A. eburnea GLM-1 T , and A. pretoriensis DSM 44654 T , respectively. Based on the phenotypic, chemotaxonomic, and genomic data, strain MEP2-6 T could be officially assigned to a novel species within the genus Amycolatopsis, for which the name Amycolatopsis solani sp. nov. has been proposed. The type strain is MEP2-6 T (=JCM 36309 T =TBRC 17632 T =NBRC 116395 T ). Amycolatopsis solani MEP2-6 T is strongly proven to be a non-phytopathogen of potato scab disease because stunting of seedlings and necrotic lesions on potato tuber slices were not observed, and it has no core biosynthetic genes associated with the BGCs of phytotoxins-inducing scab lesions. Furthermore, comparative genomics can ostensibly provide a better understanding of the genetic mechanisms that enable A. solani MEP2-6 T to adapt to the plant endosphere. Importantly, the strain smBGCs accommodates 33 smBGCs encoded for several bioactive compounds, which could be beneficially applied in the fields of agriculture and medicine. Consequently, strain MEP2-6 T could be a promising candidate as a novel biocontrol agent and antibiotic producer.